CONSEQUENCES OF AMBIGUOUS REGULATION OF THE RIGHT OF CONTRACTUAL PLEDGE IN MACEDONIAN PROPERTY LAW - Przheska, Tina; Živkovska, Rodna; Lalevska, Tea (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
In the legal system of the Republic of North Macedonia, the right of contractual pledge has been regulated since 2003 by a special (subject-specific) legislative act which includes detailed provisions on the acquisition and application of the right of contractual pledge. The Contractual Pledge Act (2003) was intended to compensate for the lack of provisions on the right of contractual pledge in the Ownership and Other Real Rights Act. However, the regulation of the right of contractual pledge in the Contractual Pledge Act has proven insufficient and, in certain situations, inadequate for application in legal practice. The Contractual Pledge Act contains ambiguous provisions that call into question the legal certainty in exercising the rights of the pledge creditor and the debtor. Some provisions violate the principle of party equality in favour of the pledge creditor, at the detriment of the rights of the pledge debtor. The authors critically analyse the ambiguous provisions on the right of contractual pledge to demonstrate that the Macedonian legislator has opted for restrictive and somewhat controversial regulation that contemporary legal systems tend to abandon.
Keywords: property; contractual pledge; real property law; North Macedonia